Syntheses of [Pt6(CO)8(SnCl2)(SnCl3)4]4– and [Pt6(CO)8(SnCl2)(SnCl3)2(PPh3)2]2– Platinum–Carbonyl Clusters Decorated by SnII Fragments. Issue 24 (29th July 2016) - Bortoluzzi, Marco; Ceriotti, Alessandro; Cesari, Cristiana; Ciabatti, Iacopo; Della Pergola, Roberto; Femoni, Cristina; Iapalucci, Maria Carmela; Storione, Alba; Zacchini, Stefano
Abstract : The reaction of [Pt6 (CO)6 (SnCl2 )2 (SnCl3 )4 ] 4– (1 ) with CO under atmospheric pressure resulted in the new [Pt6 (CO)8 (SnCl2 )(SnCl3 )4 ] 4– (2 ) cluster by the addition of two CO ligands and the elimination of a stannylene SnCl2 group. In turn, 2 reacted with 2 equivalents of PPh3 under a CO atmosphere to afford [Pt6 (CO)8 (SnCl2 )(SnCl3 )2 (PPh3 )2 ] 2– (3 ) by elimination of two stannyl [SnCl3 ] – ligands. Conversely, the reaction of2 with 2 equivalents of PPh3 under a N2 atmosphere resulted in a species tentatively formulated as [Pt6 (CO)5 (SnCl2 )2 (SnCl3 )2 (PPh3 )2 ] 2– (4 –5 CO) on the basis of 13 C NMR, 31 P NMR spectroscopy and ESI‐MS studies. Compounds2 –4 were spectroscopically characterized by IR spectroscopy and multinuclear ( 13 C and 31 P) variable‐temperature NMR spectroscopy. The crystal structures of2 and3 were determined by means of single‐crystal X‐ray diffraction, and their bonding was computationally investigated by DFT calculations. The possible structure of4 –5 CO was predicted by means of DFT methods. Abstract : The stepwise addition of CO and PPh3 to [Pt6 (CO)6 (SnCl2 )2 (SnCl3 )4 ] 4– results in the new [Pt6 (CO)8 (SnCl2 )(SnCl3 )4 ] 4– and [Pt6 (CO)8 (SnCl2 )(SnCl3 )2 (PPh3 )2 ] 2– bimetallic clusters. These clusters show perfect segregation of the two metals and are composed of a zero‐valent Pt6 core decorated on the surface by CO, PPh3, SnCl2, and [SnCl3 ] – ligands.